O (politycznych) mechanizmach selekcji tekstów literackich dla czytelnika zagranicznego - Regina Solová (Ksiegarnia Akademicka Publishing, 2019)
Political Mechanisms of the Selection of Literary Texts for Foreign Readers. Example of the Monthly Polska: czasopismo ilustrowane in the 1950s